Macedonian tourist product: Current status and perspectives - Violeta Milenkovska; Zoran Strezovski; Angela Milenkovska (UTMS Journal of Economics, 2015)
The main aim of this paper is about Macedonian tourist offer. Many countries have developed their own tourist product in direction to attract more tourist in destination. They work intensively to rebuild attractive factors, to improve communications and increase quality accommodation facilities. The quality tourist product has strong influence of the destination attracting a lot of foreign tourist. In 2008, Macedonian government put tourism product as a main focus in its policy. The government make a essential document Strategy for development of Tourism in Macedonia from 2009-2013. The results of that document give some actions how to be improve Macedonian tourist product. Upon the preparation of the strategy for the development of tourism, the tourist economy with its experience was not actively involved. Because of that, strategy was not implemented completely. This paper presents an action research conducted on a sample of 65 tourist stockholders (travel agencies and hotels) in Macedonia in 2013. This study analyze Macedonian tourist offer. What is done and what should be done in the future in name what other countries have undertaken regarding the aspect of promotion of their tourist product, concerning promotion of their tourist destination and what Macedonia has undertaken and should undertake regarding that aspect.
Keywords: L83; 330; tourism; foreign tourists; tourist offer; Macedonia; perspectives